Analisis Penjadwalan Kegiatan Produksi pada PT. Muliaglass Float Division dengan Metode Forward dan Backward Scheduling - Elika Patricia; Hadi Suryono (Universitas Bunda Mulia, 2017)
Carry out the work effectively and efficiently to the desired goal is achieved by all the company's management. Therefore an understanding of the concept of scheduling is very important, so that the practitioner should know when starting a job and when it ended. Scheduling is an important activity within the company. The technique used depends on production volume, product variations, operating conditions, and the complexity of the work itself. Regardless of the type of company, every company needs to do the scheduling as possible in order to obtain maximum utility from resource production.Keywords: Scheduling, Production, Planning